The impact of strategic planning on knowledge sharing in the Salah Al-Din Health Department in Iraq from the point of view of administrative leaders 2022 - Mahdi, Anas Khleel; Idriss, Elfadil Timan; Ali, Malikelneem Muhammad (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of this research is to identify the impact of strategic planning on knowledge sharing, Salah al-Din Health Department from the point of view of administrative leaders. to achieve the objectives of the study, the analytical descriptive approach was followed by developing a questionnaire and distributing it to the study sample of (358) employees working in the administrative leadership in the Salah al-Din Health Department in Iraq.Statistical methods were used within the Statistical Program for Social Sciences (SPSS) to process data, extract arithmetic means and standard deviations, and apply the multiple regression equation. The study showed a set of results, the most prominent of which are: There is a statistically significant effect at the significance level (α≤0.05) of strategic planning on knowledge sharing, Salah al-Din Health Department from the point of view of administrative leaders. The study recommended a set of recommendations, the most important of which are: the need for Iraqi government institutions to be interested in achieving a balance between the interim needs and the future vision; and that is by supporting the element of flexibility in preparing the vision and making it more renewable.
Keywords: Strategic Planning; Knowledge Sharing; Salah Al-Din Health Department; Administrative leaders